Assessing inclusion of trans people in HIV national strategic plans: a review of 60 high HIV prevalence countries. Issue 11 (11th November 2021) - Sherwood, Jennifer; Lankiewicz, Elise; Castellanos, Erika; O'Connor, Naomhán; Theron, Liesl; Restar, Arjee
Abstract: Introduction: Trans people are disproportionately impacted by HIV yet have not been adequately prioritized in national HIV responses or policy documents. This review aims to understand the extent of meaningful inclusion of trans people in national strategic plans (NSPs) for HIV/AIDS as an essential step in ensuring that HIV policy aligns with epidemiologic data, and trans‐specific programming is funded, implemented and sustained. Methods: HIV NSPs from 60 countries, across five global regions, were assessed for the level of inclusion of trans populations between January and March 2021. The most recently available NSP for each country, published after 2011, was obtained through publicly accessible online sources or through researcher networks. Data were manually extracted from NSPs using a framework of indicators focusing on trans inclusion in these five major sections of NSPs: (1) narratives; (2) epidemiological data; (3) monitoring and evaluation (M&E) indicators and targets; (4) activities; and (5) budgets. Results and discussion: Within all reviewed NSPs, 65.0% (39/60) mentioned trans people in at least one of the five key sections but only 8.3% (5/60) included trans people in all five key sections. Trans people were more commonly mentioned in the background/narratives of NSPs (61.7%, 37/60) but less commonly included NSP activities (38.3%, 23/60), in M&E indicators and targets (23.7%, 14/60), in epidemiological data (20.0% 12/60), and in NSP budgets (13.3%, 8/60). Countries in the Asia and Pacific region most frequently included trans people in all five key sections (38%, 5/13), while no countries in Eastern and Southern Africa included trans people in all NSP sections. Conclusions: This analysis finds substantial gaps in the inclusion of trans populations in NSPs globally. Results highlight the pressing need for states, technical partners, and international funders to engage with trans communities to improve trans‐inclusion in all key sections of NSPs. Trans inclusion in NSPs is an essential step towards reaching the populations most at risk of HIV and ultimately achieving country‐level epidemic control.